Vertical and horizontal distributions of 137Cs on paved surfaces affected by the Fukushima Dai-ichi Nuclear Power Plant accident. (June 2020) - Yoshimura, K.; Watanabe, T.; Kurikami, H.
Abstract: Vertical and horizontal distributions are fundamental for sampling and in-situ gamma spectrum measurement strategies. The distributions of 137 Cs were investigated for paved surfaces affected by the Fukusima Dai-ichi Nuclear Power Plant accident. Additionally, the effects of the distributions on the measurement uncertainties of in-situ spectrometry were evaluated. Relaxation mass depth, representing the depth profile of 137 Cs, was estimated to be less than 0.23 g cm −2 . Variation in the relaxation mass depth, of 0.1–0.23 g cm −2, led to a minor error (less than 5%) in the spectral analysis of the 137 Cs inventory (activity per unit area, kBq m −2 ). The 137 Cs inventory, within a 20 × 20 m square of 400 cells each measuring 1 m 2, showed an uneven distribution with large variation; coefficient of variation ranged from 54 to 136% of geometric average inventory of 424 kBq m −2 . Increasing the grid size decreased 137 Cs inventory variation among cells, revealing the relationship between instrument field of view and the spatial uncertainty of the results of in-situ gamma spectrometry. Highlights: Relaxation mass depth of 137 Cs on impermeable asphalt was less than 0.23 g cm −2 . Uncertainty of the relaxation mass depth results in minor error of 137 Cs activity on paved surface. Horizontal distribution of 137 Cs varied largely within 20 m square. Relation between fields of view and uncertainty of 137 Cs activity was evaluated.